2021
DOI: 10.7759/cureus.20602
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis Can Be the Sole Presentation in Celiac Disease

Abstract: Celiac disease, an autoimmune condition causing gluten intolerance and disrupted absorption of nutrients, predisposes to osteoporosis. The release of pro-inflammatory cytokines, calcium malabsorption, and the activation of osteoclasts represent the main mechanisms responsible for bone derangement. This is evidenced by the low T-score on dual-energy x-ray absorptiometry (DXA) scans in these patients. However, these changes are reversible with the early initiation of a gluten-free diet. Hence, it is important fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
(15 reference statements)
0
3
0
1
Order By: Relevance
“… 23 However, in a recent study, the sole presentation of CD was osteoporosis without any gastrointestinal symptom. 24 Thus, many researchers now advise to screen patients with refractory osteoporosis for underlying CD. Although the precise relationship between CD and excessive bone loss is unknown, as the condition affects the intestines, the absorption of calcium and vitamin D gets difficult; both of which are crucial for preserving bone density.…”
Section: Discussionmentioning
confidence: 99%
“… 23 However, in a recent study, the sole presentation of CD was osteoporosis without any gastrointestinal symptom. 24 Thus, many researchers now advise to screen patients with refractory osteoporosis for underlying CD. Although the precise relationship between CD and excessive bone loss is unknown, as the condition affects the intestines, the absorption of calcium and vitamin D gets difficult; both of which are crucial for preserving bone density.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, it has been reported that patients could show osteoporosis with elevated serum alkaline phosphatase levels (ALP) and hyperparathyroidism as the sole presentation of CD [30]. Walker et al suggested that forearm bone density measurement, usually not screened when assessing BMD, is of aid to identify osteoporosis; it may be performed in addition to hip and lumbar spine BMD evaluation, which alone tends to underestimate the prevalence of osteoporosis [31].…”
Section: Pathologic Bone Alterations In Celiac Diseasementioning
confidence: 99%
“…Co więcej, należy pamiętać, że u pacjentów pediatrycznych klasyczny obraz celiakii obejmuje nie tylko bóle brzucha i wzdęcia, ale także utratę masy ciała i zahamowanie wzrostu. Opóźnione dojrzewanie, brak miesiączki czy zaburzenia rozwojowe powinny skłaniać lekarzy do poszerzenia diagnostyki w kierunku celiakii i jak najszybszego włączenia leczenia [17].…”
Section: Objawyunclassified